Downtown Film and TV Culture 1975-2001: 1975–2001 - Hawkins, Joan (Intellect, Limited, 2015)
Downtown Film and TV Culture, 1975-2001 brings together essays by filmmakers, exhibitors, cultural critics and scholars from multiple generations of the New York Downtown scene to illuminate individual films and filmmakers and explore the impact of the historic downtown scene on contemporary culture.
https://katalog.adlr.link/Record/76-EBC2091477